Karakteristik Wanita dengan Penderita Kista Ovarium - Deybi Julianti Napitu; Rini Handayani; Ira Marti Ayu; Mayumi Nitami (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Ovarian cysts are one of the reproductive organ diseases in women. This study aims to determine the characteristics of women with ovarian cysts at Hospital X in Jakarta from 2022 to June 2025. This research uses a case series study design with a sample size of 70 women diagnosed with ovarian cysts. The sampling technique used is total sampling. Data will be analyzed using univariate analysis. This study will be conducted from May to August 2025. The univariate results show that the highest proportion of respondents is aged 20-49 years (70.0%), with a classification of neoplastic cysts (100.0%), respondents with the highest education level being high school/vocational school (65.7%), the highest parity category being multipara (77.1%), the category of women with irregular menstrual cycles being (75.5%), and the highest employment category being working women (64.5%). Additionally, women using hormonal contraceptives (71.4%) and those with a family history of ovarian cysts (71.4%) were noted. The highest menarche age category was among women who experienced menarche at <12 years (62.9%) and women who are obese (61.4%). Based on the results of this study, it is hoped that women will undergo screening for the early detection of ovarian cyst disease